Specific inhibition of glutamine synthase involved in the metabolic pathway of amino acids is associated with anti-arthritic effects of sinomenine hydrochloride - Li, Gejing; Su, Zhaoli; Tang, Yuanyuan; Huang, Hong; Zhang, Junlan; Lin, Ye; Zhang, Qin; Cai, Xiong (Frontiers in Cell and Developmental Biology, 2025)
Sinomenine (SIN) is the key bioactive alkaloid isolated from Sinomenium acutum which has been prescribed commonly in Chinese medicine for managing rheumatic disorders. Despite its clinical relevance, the metabolic mechanisms underlying its therapeutic effects remain insufficiently explored, particularly in relation to amino acid dysregulation in rheumatoid arthritis (RA). The anti-arthritic efficacy of sinomenine hydrochloride (SH) was tested in adjuvant-induced arthritis in rats utilizing clinical scoring and histological analysis. Plasma metabolomics was employed to identify SH-mediated changes in amino acid-related metabolic profiles. Key metabolic pathways and targets were examined using computational docking and surface plasmon resonance (SPR) assay. The interaction of SH and molecular targets was further validated in RA fibroblast-like synoviocytes (RA-FLS). SH at dose of 100 mg/kg significantly alleviated disease progression of AIA, as evidenced by reduced paw edema and inhibited histopathological changes. Metabolomic analyses identified 94 potential plasma biomarkers linked to pathways of valine/leucine/isoleucine biosynthesis, glycine/serine/threonine metabolism, phenylalanine metabolism, and alanine/aspartate/glutamate metabolism. Molecular docking and SPR identified that SH specifically targeted the glutamine synthase (GS/GLUL) (KD = 7.12 μM). Experimental validation confirmed that SH (50–200 μM) significantly inhibited GS activity and GLUL expression and consequently decreased glutamine levels in RA-FLS. In conjunction SH exerts significant anti-arthritic effects, partly by modulating the metabolic profiles of related amino acids via selective inhibition of GS-mediated de novo Gln synthesis.